2021
DOI: 10.3390/genes12020229
|View full text |Cite
|
Sign up to set email alerts
|

Whole Exome Sequencing Reveals a Novel AUTS2 In-Frame Deletion in a Boy with Global Developmental Delay, Absent Speech, Dysmorphic Features, and Cerebral Anomalies

Abstract: Neurodevelopmental disorders (NDDs) are a group of highly prevalent, clinically and genetically heterogeneous pediatric disorders comprising, according to the Diagnostic and Statistical Manual of Mental Disorders 5th edition (DSM-V), intellectual disability, developmental delay, autism spectrum disorders, and other neurological and cognitive disorders manifesting in the developmental age. To date, more than 1000 genes have been implicated in the etiopathogenesis of NNDs. Among them, AUTS2 (OMIM # 607270) encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Finally, AUTS2 encodes the autism susceptibility candidate 2 protein that is involved in neural migration and neurogenesis. It has been reported that mutations in this gene are associated with neurological and skeletal abnormalities [ 17 ], suggesting the possible link of this gene to skeletal development.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, AUTS2 encodes the autism susceptibility candidate 2 protein that is involved in neural migration and neurogenesis. It has been reported that mutations in this gene are associated with neurological and skeletal abnormalities [ 17 ], suggesting the possible link of this gene to skeletal development.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated the frequency of the 32 items included in the ASSS in patients currently reported in the literature. For that, only 9 studies with a comprehensive description of the phenotype were considered: papers by Beunders et al, 2016 [ 5 ], which includes aggregated data from their two previous reports [ 4 , 6 ] as well as from other authors [ 10 , 14 , 15 , 16 , 17 , 27 , 28 , 29 ] and other seven studies [ 8 , 9 , 11 , 18 , 19 , 20 , 21 ]. The total number of patients reported by such studies was 61 but the number of patients evaluated for the 32 items was highly variable and ranged from 11 to 61 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…More than 60 patients with AUTS2 syndrome have been described to date [4][5][6][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. These patients mostly carry de novo intragenic or exonic deletions, whereas loss-of-function small variants are not as frequently found in the literature [4,5,9,11,[19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations